Introduction of Microgreen Planting Techniques to Elementary School Children in Bantaragung Village, Sindangwangi, Majalengka, West Java - Salsabila Insani Latif; Sri Rum Giyarsih Tidak ada (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Urban farming and the concept of microgreens are gaining increasing attention in efforts to introduce sustainability and healthy eating patterns to the community. Amidst the challenges of awareness about the importance of consuming fresh vegetables, elementary school children are potential agents of change who are important in forming a generation that cares and is responsible for the environment. This community service aims to introduce microgreen planting techniques to elementary school children in Bantaragung Village, Sindangwangi District, Majalengka Regency, West Java Province. The method is carried out through direct practice activities in elementary schools, with interactive learning, direct observation, and active participation of students. The results show that the introduction of microgreen planting techniques positively influences children's awareness of the importance of consuming fresh vegetables and playing a role in environmental sustainability. Children show high enthusiasm for this activity and understand the process of plant growth better. In addition, the introduction of urban farming through microgreens also helps teach them about responsibility and cooperation in caring for plants. Thus, this community service makes an important contribution to the development of agriculture and environmental education in Bantaragung Village. The results of this community service can be an inspiring example for similar efforts in educating elementary school children in other areas about the importance of urban farming and consuming fresh vegetables for a more sustainable future.